Comparison of a Synthetic Antithrombin III-binding Pentasaccharide and Standard Heparin as an Adjunct to Coronary Thrombolysis - Pislaru, Sorin V.; Pislaru, Cristina; Zhu, Xu; Arnout, Jef; Stassen, Tony; Vanhove, Philippe; Herbert, Jean-Marc; Meuleman, Dirk G.; Van de Werf, Frans (Thrombosis and Haemostasis, 1998)
The effects on alteplase-induced thrombolysis of the synthetic ATIII-binding pentasaccharide SR90107A/ORG 31540 (synthetic pentasaccharide, SP) and of standard heparin (SH) were compared in a copper coil model of coronary artery thrombosis in 6 groups of 10 dogs. After 1 h of occlusion, all animals received intravenously alteplase and aspirin, and were randomly assigned to a 2 h infusion of either saline, or one of two doses of SH (100 IU/kg bolus plus 50 IU/kg/h infusion, or 200 IU/kg bolus plus 100 IU/kg/h infusion), or one of three doses of SP (100 nmol/kg bolus plus 50 nmol/kg/h infusion, 200 nmol/kg bolus plus 100 nmol/kg/h infusion, or 400 nmol/kg bolus plus 200 nmol/kg/h infusion). Coronary angiography was performed every 10 min for 4 h. Appropriate doses of SP and SH enhanced alteplase-induced thrombolysis to a similar extent. In contrast, SP was devoid of any anti-IIa activity or aPTT prolongation.